International security an analytical survey - Sheehan, Michael (Lynne Rienner Publishers, 2005)
Michael Sheehan provides a survey of the varied positions that scholars have adopted in interpreting 'security'. In conclusion, revealing his own interpretation of security, he makes the case for a postpositivist conception that links human emancipation, justice, and peace.
Keywords: Security, International